2023
DOI: 10.1021/acs.inorgchem.3c00309
|View full text |Cite
|
Sign up to set email alerts
|

Zinc-Catalyzed Chemoselective Reduction of Nitriles to N-Silylimines through Hydrosilylation: Insights into the Reaction Mechanism

Abstract: The N,N′-chelated conjugated bis-guanidinate (CBG) supported zinc hydride (Zn-1) pre-catalyzed highly challenging chemoselective mono-hydrosilylation of a wide range of nitriles to exclusive N-silylimines and/or N,N′-silyldiimines is reported. Furthermore, the effectiveness of pre-catalyst Zn-1 is compared with another pre-catalyst analogue, i.e., DiethylNacNac zinc hydride (Zn-2), to know the ligand effect. We observed that pre-catalyst Zn-1 shows high efficiency and better selectivity than pre-catalyst Zn-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…40 Recently, Nembenna and co-workers showed that Zn–H could catalyze the hydrosilylation of nitriles to imines utilizing diphenylsilane in THF solvent under mild conditions. 41…”
Section: Introductionmentioning
confidence: 99%
“…40 Recently, Nembenna and co-workers showed that Zn–H could catalyze the hydrosilylation of nitriles to imines utilizing diphenylsilane in THF solvent under mild conditions. 41…”
Section: Introductionmentioning
confidence: 99%
“…The significance of hydrosilylation of C–N triple bonds in organonitriles is well-established, as the resulting organosilicon products have a wide range of applications, particularly in organic synthesis. The hydrosilylated products formed, such as disilylamines, are used as precursors for the synthesis of polymers containing Si–N bonds, such as polysilazanes and polysilsesquiazanes, which are used as precursors for ceramic applications. , N -Silylamines are synthons for various catalytic transformations, including C–N bond-forming cross-coupling reactions; meanwhile, N -silylimines are well-established for their use in enantioselective synthesis. However, the catalytic monoaddition of a Si–H bond to a C–N triple bond continues to be a synthetic challenge, which makes this transformation a key target for new catalysts. Controlling the selectivity of this transformation is particularly challenging as the initially formed N -silylimines, R 3 Si–NCHR, may readily undergo a second addition to form the double-addition product disilylamines, (R 3 Si) 2 NCH 2 R. However, a small number of metal- and nonmetal-based , catalysts for monohydrosilylation of nitriles to form N -silylimines selectively have begun to emerge recently. The interaction of hydrosilanes with transition metals has been well-documented in the series of reviews by Corey. The catalytic monohydrosilylation of organonitriles with monohydrosilanes to synthesize N -silylimines selectively was achieved by Nikonov and co-workers using a cationic ruthenium complex [CpRu­(NCMe) 2 (P i Pr 3 )]­[B­(C 6 F 5 ) 4 ] as a precatalyst with almost quantitative yields after 0.3 to 48 h at ambient temperature with a 4–5 mol % catalytic loading (Scheme a) .…”
Section: Introductionmentioning
confidence: 99%